ENERGY EFFICIENCY AND SUSTAINABILITY: ANALYSIS OF INDICATORS OF GENERATION, ENERGY QUALITY, AND ENVIRONMENTAL MANAGEMENT OF THE UNIEVANGÉLICA PHOTOVOLTAIC PLANT IN ANÁPOLIS, GOIÁS (2020-2023) (CIPEEX, 2025)
This study is part of the thesis presented to the Graduate Program in Society, Technology, and Environment at the Evangelical University of Goiás (PPGSTMA), with the aim of obtaining a PhD in Environmental Sciences. The research evaluated the energy efficiency and sustainability of the UniEVANGÉLICA (UF-Uni) Photovoltaic Plant, using energy generation data from 2020 to 2023, in addition to an energy analyzer to verify the quality of the electricity generated. The theoretical studies were conducted in the PPGSTMA computer labs, while the practical investigations took place at the Photovoltaic Energy Efficiency Laboratory (LEEFOTO). The results showed that, after 72 years of existence, the Associação Educativa Evangélica (AEE) took a decisive step toward financial and energy sustainability, consolidating its institutional policies and values with the implementation of UF-Uni. The research showed that, globally, photovoltaic plants prioritize financial and performance indicators over environmental ones, highlighting the search for profitability. The use of statistical tools and time series proved effective in monitoring and projecting energy generation, highlighting the importance of university governance and artificial intelligence. It was found that the energy generated by UF-Uni meets the standards of the National Electric Energy Agency (ANEEL), although productivity was below expectations. The study recommends regular maintenance and the adoption of advanced technologies to ensure greater energy efficiency, proposing a model aligned with the Sustainable Development Goals (SDGs) and ESG principles, offering a replicable solution for other institutions and companies.
Keywords: Governance; Sustainability; Renewable energy; Energy efficiency